A fluorescent redox sensor with tuneable oxidation potential - Kierat, Radoslaw; Thaler, Birgit; Krämer, Roland (Bioorganic & medicinal chemistry letters, 2010)
A fluorescent redox sensor was prepared by attachment of hydroquinones to the fluorophore rhodamine B; fluorescence is reversibly modulated by hydroquinone-centered chemical redox reactions, and oxidation potential of the sensor is tuneable by variation of hydroquinone structure.
Online veröffentlicht am 6. Juni 2009
Gesehen am 09.03.2023